THE WAR OF EMPYRIA (BOOK ONE) - Bramantyo Januar; Budi Darma (Kata Kita: Journal of Language, Literature, and Teaching, 2016)
In this creative work, the author would like to give picture of the reality and phenomenon happening in the life of humanity through a fantasy novel. The main theme that is used in this creative work is ambition. In this project, he would like to show how ambition can drive each individual into taking any action that will lead them closer to their goals. He would also explore how the bloom of ambitions can be triggered by many things such as revenge, sense of justice, or dissatisfaction. The purpose of this novel is to show how every person has the natural existence of ambition in themselves. However, sometimes the reasons of those ambitions for every person are differing in each other, and in some certain states can lead to a conflict